HEIGHTENED TEST ANXIETY AMONG YOUNG CHILDREN: ELEMENTARY SCHOOL STUDENTS' ANXIOUS RESPONSES TO HIGH‐STAKES TESTING. Issue 5 (6th March 2013) - Segool, Natasha K.; Carlson, John S.; Goforth, Anisa N.; von der Embse, Nathan; Barterian, Justin A.
<x xml:space="preserve">Abstract</x> This study explored differences in test anxiety on high‐stakes standardized achievement testing and low‐stakes testing among elementary school children. This is the first study to directly examine differences in young students' reported test anxiety between No Child Left Behind (NCLB) achievement testing and classroom testing. Three hundred thirty‐five students in Grades 3 through 5 participated in the study. Students completed assessments of test anxiety following NCLB testing and typical classroom testing. Students reported significantly more overall test anxiety in relation to high‐stakes testing versus classroom testing on two measures of test anxiety, effect sizes r = −.21 and r = −.10. Students also reported significantly more cognitive (r = −.20) and physiological (r = −.24) symptoms of test anxiety in relation to high‐stakes testing. This study adds to the test anxiety literature by demonstrating that students experience heightened anxiety in response to NCLB testing.